A systematic analysis of metadata application profiles of learning object repositories in Europe - Zervas, P.; Kalamatianos, A.; Sampson, Demetrios (2014)
© Springer-Verlag Berlin Heidelberg 2014. Over the past years, several initiatives have emerged worldwide towards the provision of open access to educational resources, in the form of learning objects (LOs). The main objective of such initiatives is to support the process of organizing, classifying, and storing LOs and their associated metadata in Web-based repositories which are called learning object repositories (LORs). Within this framework, popular ways for describing LOs are the Dublin Core Metadata Element Set (DCMES) and the IEEE Learning Object Metadata (LOM) Standard. However, it has been recognized that it is not possible for generic standards such as DCMES and IEEE LOM to be used to fully meet community and context-specific users’ needs. This has lead to the emergence of the metadata application profile (AP) concept and a number of metadata APs have been developed, which are used by a variety of LORs that are currently operating online. On the other hand, with many LORs implemented based on different metadata APs, the issue of metadata interoperability between these LORs is crucial. In this chapter, we focus on metadata interoperability of different LORs that have been developed by institutions, communities, or consortiums in Europe. More specifically, we present the results of a systematic analysis of metadata APs used in nineteen (19) European LORs, and we provide recommendations for future development of metadata APs.